2020
DOI: 10.3390/nu12030664
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Dark Chocolate on Retinal and Choriocapillaris Perfusion in Young, Healthy Subjects Using Optical Coherence Tomography Angiography

Abstract: 1) Aim: Contrasting results have been published on the effect of dark chocolate on visual function. The aim of this study was to evaluate retinal and choriocapillaris perfusion, using optical coherence tomography angiography (OCT-A), and visual function in healthy subjects following dark chocolate ingestion. (2) Methods: This prospective randomized study was carried out on 18 healthy young subjects at the St. Andrea Hospital, Sapienza, University of Rome. Visual acuity assessment and a complete ophthalmologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This technology enables the segmentation of choroid-retinal vascularization into distinct layers, including the superficial capillary plexus (SCP) and the deep capillary plexuses (DCP), the outer retina, and the choriocapillaris (CC). Figure 4 shows the OCTA segmentation into SCP, DCP, and CC layers [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology enables the segmentation of choroid-retinal vascularization into distinct layers, including the superficial capillary plexus (SCP) and the deep capillary plexuses (DCP), the outer retina, and the choriocapillaris (CC). Figure 4 shows the OCTA segmentation into SCP, DCP, and CC layers [ 68 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This technology enables the segmentation of choroid-retinal vascularization into distinct layers, including the superficial capillary plexus (SCP) and the deep capillary plexuses (DCP), the outer retina, and the choriocapillaris (CC). Figure 4 shows the OCTA segmentation into SCP, DCP, and CC layers [68,69]. A recent study examined the role of OCTA in evaluating CCHs, underlying how it can provide insight into lesion characteristics by analyzing density, flow, and vascular patterns.…”
Section: Spectral Domain Optical Coherence Tomography (Sdoct)mentioning
confidence: 99%
“…Indeed, flavanols (found in a variety of fruits, vegetables, and cocoa products) offer a promising alternative treatment for diabetes mellitus due to their plentiful antioxidant capabilities (higher phenolic compounds) [71]. These nutraceuticals' mechanisms for improving diabetes and retinal function include, but are not limited to, increasing insulin sensitivity, lowering blood pressure and inflammatory processes, and preventing platelet activation and aggregation [71,88]. It would be excellent to examine the preventive effects of cocoa (flavanol nutraceutical) against hyperglycemia-induced retinal dysfunctions in adult Sprague Dawley rats in order to better understand the mechanisms involved in the development and advanced state of diabetic retinopathy.…”
Section: (E) Phytochemicalsmentioning
confidence: 99%
“…The choroid, a vital anatomical structure within the human eye, serves as the primary source of blood supply to the outer retina [5][6][7] . Numerous studies have indicated a correlation between sleep patterns and the onset of myopia, with the impact of sleep on the choroid potentially serving as a contributing factor [8][9][10][11][12] .The choroid demonstrates a reduced thickness in eyes a icted with myopia when juxtaposed with eyes a icted with astigmatism and hyperopia 13 .This has prompted several studies to propose that choroidal thickness could serve as an indicator of myopia progression, although this correlation has not been de nitively established through quantitative analysis. Therefore, thickening of the choroid may potentially delay the onset of myopia, even if such thickening is only temporary.…”
Section: Introductionmentioning
confidence: 99%